2011
DOI: 10.4103/0972-124x.84383
|View full text |Cite
|
Sign up to set email alerts
|

To assess the effectiveness of a chlorhexidine chip in the treatment of chronic periodontitis: A clinical and radiographic study

Abstract: Context:Controlled local delivery of disinfecting agents has been demonstrated to be efficient in improving the outcome of periodontal therapy.Aims:The aim of the present study was to evaluate the efficacy of a controlled-release biodegradable chlorhexidine chip (Periocol CG) when used as an adjunct to scaling and root planing in the treatment of periodontitis.Settings and Design:The study was carried out as randomized controlled two-group parallel clinical trial.Materials and Methods:Forty patients in the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
7
22
0
1
Order By: Relevance
“…The novelty and utility of this agent warrants further research. These clinical trials have attested the safety and non-toxicity of the product reporting no serious adverse effects [17][18][19][20]. The clinical efficacy of this chip in reducing probing depth, bleeding on probing and clinical attachment loss has been reported [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novelty and utility of this agent warrants further research. These clinical trials have attested the safety and non-toxicity of the product reporting no serious adverse effects [17][18][19][20]. The clinical efficacy of this chip in reducing probing depth, bleeding on probing and clinical attachment loss has been reported [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The drug delivery agent used here is a small orange-brown rectangular chip which contains approximately 2.5mg of chlorhexidine in a biodegradable matrix of fish collagen type I derived from the air bladder of fresh water fishes [16,17]. If needed the chip was trimmed with a scalpel.…”
Section: Randomization [28]mentioning
confidence: 99%
“…Controlled delivery system has duration of drug release more than 24 hours. The effects of locally delivered controlled-release chlorhexidine have been shown to be evident upto 11weeks [25] [12,[26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Perio chip releases chlorhexidine in vitro in a biphasic manner, initially releasing approximately 40% of the chlorhexidine within the first 24 hours, and then releasing the remaining chlorhexidine in an almost linear fashion for 7-10 days. Grover et al reported that chlorhexidine chip and SRP resulted in a clinically significant improvement in PPD and CAL compared with SRP alone 26 . Jagadish Pai et al showed that Clinically significant reduction in PPD, BOP and CAL by using chlorhexidine varnish and chlorhexidine chip along with SRP but the results were not statistically significant when compared with SRP alone 27 .…”
Section: Ointment:-mentioning
confidence: 99%